The Impact of Tri Dharma Performance on Higher Education Performance Based on Monitoring Results - Sugiarti, Endang (AKADEMIK: Jurnal Mahasiswa Humanis, 2022)
The achievement of higher education performance cannot be separated from the performance of the lecturers' tri dharma. This is stated in the institution's accreditation assessment indicators. Thus, there is a linear relationship between lecturer performance and university performance, so it is necessary to conduct research so that it can be taken into consideration for universities to be able to pay attention to aspects that affect lecturer performance. To be able to reveal this phenomenon, this study establishes a qualitative approach, which is an attempt to present valid information as the basis for disclosure. In its interpretation, descriptive analysis technique is used. In collecting data using secondary data, namely analyzing the results of SPMI activities carried out by the Quality Assurance Institute of Pamulang University and interviews. The results showed that the performance of the lecturers' tri dharma was in the good category with a percentage of 90%. This confirms that the good performance of lecturers can contribute to the good performance of the university. However, several things that are still a note for improvement in the institution are the lack of academic positions of head lector and professor, there are still many lecturers who have not received professional certification, and the lack of awards.